Extent of non-adherence and non-persistence in asthma patients: analysis of a large claims data set. (7th April 2022) - Hardtstock, Fränce; Maywald, Ulf; Timmermann, Hartmut; Unmüßig, Victoria; Müller, Sabrina; Wilke, Thomas; Welte, Robert
Abstract: Objective: The objective of this study was to assess non-adherence (NA) and non-persistence (NP) to long-acting asthma medications in Germany by differentiating between measurement of NA in periods of therapy continuation and measurement of NP in therapy-naïve patients. Methods: We analyzed treatment adherence to long-acting asthma medication using German claims data for periods of treatment continuation based on the medication possession ratio (MPR) and the proportion of days covered. Persistence was assessed in treatment-naïve patients. Outcomes were observed from the date of the first to the last prescription within a 12-month period. Both NA and NP analyses considered prescription supply, using either defined daily dosages, or prescribed daily dosages derived from a medical chart review. Results: We identified 52, 508 asthma patients (mean age: 40.1, 58.4% female) who received at least two long-acting asthma prescriptions within 12 months; 50, 660 treatment-naïve patients were included in the NP analysis (mean age: 39.7, 58.8% female). The mean 12-month MPR was 38.5% (89.4% NA according to MPR ≤ 80%) and the average proportion of days covered was 40.4% (85.9% NA). Agent-specific MPR and NA rates varied between 31.8% (91.8% NA) and 56.2% (71.6% NA). The average weighted-MPR increased to 53.1% when using the prescribed daily dosage. Based on a  > 90-day gap definition, 86.7% of patients were considered non-persistent after 12 months (>180: 72.3%). When using prescribed daily dosages, NP rates ranged from 66.7 to 78.5%. Conclusion: High levels of treatment NA and NP indicate a substantial need to improve adherence and persistence to long-acting asthma medication in Germany.